Utylitaryzm jako możliwość etyki coachingu w doradztwie filozoficznym = Utilitarianism as a possibility of coaching ethics in philosophical counselling - Turowski, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this text is to emphasize the necessity for an ethical approach to coaching as a method of philosophical counselling. I think that necessity to deal with moral philosophy in the coaching profession is quite obvious, but I emphasize that this is not about some version of professional ethics. The point is in moral thinking itself and shaping methods and goals according to the utilitarian proposal. It has two important features for the coaching profession: first of all, it allows the application of simple rules to practice, because I think, this is the most important for coaching; secondly, utilitarianism as consequentialism emphasizes the material approach to normative ethics, which means that one never has to stick to norms just because they are categorical rules.
Keywords: etyka zawodowa; utylitaryzm; normatywizm; deontologia; obowiązki; konsekwencjalizm; prawo moralne; formalizm; materializm; professional ethics; utilitarianism; normativism; deontology; duty; consequentialism; moral law; formalism; materialism